Nutrition in acute renal failure - Guimarães, Sérgio Mussi; Cipullo, José Paulo; Lobo, Suzana Margareth Ajeje; Burdmann, Emmanuel de Almeida (São Paulo Medical Journal, 2005)
Nutritional status has been considered to be one of the possible determinants of mortality rates in cases of acute renal failure (ARF). However, most studies evaluating possible mortality indicators in ARF cases have not focused on the nutritional status, possibly because of the difﬁculties involved in assessing the nutritional status of critically ill patients. Although the traditional methods for assessing nutritional status are used for ARF patients, they are not the best choice in this population. The use of nutritional support for these patients has produced conﬂicting results regarding morbidity and mortality. This review covers the mechanisms and indicators of malnu- trition in ARF cases and the types of nutritional support that may be used.